Multiple Positive Solutions to a Kirchhoff Type Problem Involving a Critical Nonlinearity in ℝ3 - Zhong Xiao-Jing; Tang Chun-Lei (Advanced Nonlinear Studies, 2017)
In this paper, we investigate a class of Kirchhoff type problems in ℝ3{\mathbb{R}^{3}} involving a critical nonlinearity, namely,